2014
DOI: 10.5194/acp-14-10133-2014
|View full text |Cite
|
Sign up to set email alerts
|

Carbon balance of China constrained by CONTRAIL aircraft CO<sub>2</sub> measurements

Abstract: Abstract. Terrestrial carbon dioxide (CO 2 ) flux estimates in China using atmospheric inversion method are beset with considerable uncertainties because very few atmospheric CO 2 concentration measurements are available. In order to improve these estimates, nested atmospheric CO 2 inversion during 2002-2008 is performed in this study using passenger aircraft-based CO 2 measurements over Eurasia from the Comprehensive Observation Network for Trace gases by Airliner (CONTRAIL) project. The inversion system incl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
(67 reference statements)
4
25
1
Order By: Relevance
“…To estimate surface CO 2 fluxes, atmospheric transport models have been conventionally constrained by various surface measurement networks (e.g., Gurney et al, 2002;Patra et al, 2008). But due to the sparseness of the surface T. Umezawa et al: Seasonal variations of tropospheric CO 2 over Asia Pacific measurement sites in Asia, an increasing number of modeling studies that have focused on the Asian carbon budget (e.g., Patra et al, 2011;Zhang et al, 2014;Jiang et al, 2014Jiang et al, , 2016 in recent years started to incorporate CO 2 data taken by commercial airliners, such as CARIBIC (Civil Aircraft for the Regular Investigation of the atmosphere Based on an Instrument Container; Brenninkmeijer et al, 2007) and CONTRAIL (Comprehensive Observation Network for TRace gases by AIrLiner; . It has been demonstrated that by incorporating the CARIBIC and CONTRAIL data, model estimates of the Asian CO 2 fluxes have been significantly improved (Patra et al, 2011;Shirai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To estimate surface CO 2 fluxes, atmospheric transport models have been conventionally constrained by various surface measurement networks (e.g., Gurney et al, 2002;Patra et al, 2008). But due to the sparseness of the surface T. Umezawa et al: Seasonal variations of tropospheric CO 2 over Asia Pacific measurement sites in Asia, an increasing number of modeling studies that have focused on the Asian carbon budget (e.g., Patra et al, 2011;Zhang et al, 2014;Jiang et al, 2014Jiang et al, , 2016 in recent years started to incorporate CO 2 data taken by commercial airliners, such as CARIBIC (Civil Aircraft for the Regular Investigation of the atmosphere Based on an Instrument Container; Brenninkmeijer et al, 2007) and CONTRAIL (Comprehensive Observation Network for TRace gases by AIrLiner; . It has been demonstrated that by incorporating the CARIBIC and CONTRAIL data, model estimates of the Asian CO 2 fluxes have been significantly improved (Patra et al, 2011;Shirai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of an Instrument Container) 13 , CONTRAIL (Comprehensive Observation Network for TRace gases by AIrLiner) 14 15 and Asian Global Atmospheric Watch (GAW) have helped ameliorate this. CARIBIC data have been utilized in an inversion for CO 2 fluxes in South Asia 16 and CONTRAIL data in inversions focusing on Asian CO 2 fluxes 17 18 19 . These inversions 16 17 18 consistently found a net sink for South Asia of −0.11 to −0.37 PgC per year (note that a negative flux is in the direction from the atmosphere to the land/ocean, that is, a sink).…”
mentioning
confidence: 99%
“…CARIBIC data have been utilized in an inversion for CO 2 fluxes in South Asia 16 and CONTRAIL data in inversions focusing on Asian CO 2 fluxes 17 18 19 . These inversions 16 17 18 consistently found a net sink for South Asia of −0.11 to −0.37 PgC per year (note that a negative flux is in the direction from the atmosphere to the land/ocean, that is, a sink). In contrast, for Southeast Asia, one recent study 17 found a source of ∼0.45 PgC per year, while another 18 found a sink of ∼−0.28 PgC per year.…”
mentioning
confidence: 99%
“…Such experiments can be used to estimate the uncertainty reduction (see Sect. 3.2) that could potentially be achieved by assimilating more observations over or downwind from poorly constrained regions as well as the effects of a more extensive observational network on the estimated spatial and temporal variability of fluxes (e.g., Butler et al, 2010;Saeki et al, 2013b;Kadygrov et al, 2015;Jiang et al, 2014;Peters et al, 2010). They can also be used to determine the value of episodic versus continuous observations (e.g., Peters et al, 2010).…”
Section: Atmospheric Observationsmentioning
confidence: 99%
“…More broadly, evaluation against all types of independent atmospheric observations provides an additional window into the degree to which estimated fluxes capture key features of the atmospheric signal, such as the seasonal cycle, latitudinal gradients, or regional patterns of concentrations (e.g., Zhang et al, 2014;Jiang et al, 2014;Díaz Isaac et al, 2014;Pandey et al, 2016;Liu and Bowman, 2016;Johnson et al, 2016).…”
Section: Evaluation Against Unused Atmospheric Observationsmentioning
confidence: 99%